Hybrid Machine-Learning Model for Accurate Prediction of Filtration Volume in Water-Based Drilling Fluids; Applied Sciences; Vol. 14, iss. 19 - Davoodi Sh. Shadfar; Al-Shargabi M. A. T. S. Mokhammed Abdulsalam Takha Sallam; Rukavishnikov V. S. Valery Sergeevich; Mekhrad Mokhammad M.; Wood David D. A.; Al-Rubaii Mohammed M. (2024, 2024)
Title screen